IMPLEMENTASI MOTIF MERAK NGIBING PADA DESAIN EDU-FURNITURE SEKOLAH DASAR: PENDEKATAN KARAKTER ANAK MELALUI EKSPLORASI WARNA DAN BENTUK - Niken Laksitarini; Hana Faza Surya Rusyda; Sevi Nanda Dwiyati; Anisah Putri Sargo; Felliza Ayu Rachman; Nasywa Azzahra Ramadhani (Bajang Institute, 2026)
The physical environment of a classroom, including the visual quality and ergonomics of furniture, plays a crucial role in stimulating the psychological development, creativity, and character building of elementary school students. However, current elementary school learning facilities remain mostly conventional and rarely integrate local cultural wisdom as a medium for informal cultural education. This Community Service (Abdimas) program aims to design and implement an edu-furniture product in the form of a multifunctional educational shelf at Tunas Insan Mulia Elementary School by utilizing the visual potential of West Javanese traditional batik, specifically the Merak Ngibing motif. The implementation method is based on a Design Thinking approach combined with Participatory Design methods, encompassing observation, children's anthropometric analysis, motif stylization, prototype fabrication, and field testing. The child character development approach is actualized through the exploration of organic, non-geometric forms that prioritize physical safety (safety design via rounded corners), alongside bright color palette explorations (yellow, green, and blue) that psychologically stimulate cognitive focus and joy. The implementation results indicate that this edu-furniture product successfully meets the children's ergonomic comfort standards, achieving an average user satisfaction rate of 91.6%. The presence of this educational shelf not only optimizes classroom spatial function and enhances students' literacy enthusiasm in the reading corner but also effectively serves as an interactive cultural transmission medium that fosters curiosity and appreciation for local wisdom from an early age.